Attachment, Sense of Entitlement in Romantic Relationships, and Sexual Revictimization Among Adult CSA Survivors. Issue 19 (October 2021) - Brenner, Inbal; Bachner-Melman, Rachel; Lev-Ari, Lilac; Levi-Ogolnic, Mor; Tolmacz, Rami; Ben-Amitay, Galit
Insecure attachment orientations are disproportionately frequent in child sexual abuse (CSA) survivors and have been found to mediate some of the effects of CSA on adult interpersonal and romantic difficulties, including sexual revictimization (SR). A sense of relational entitlement (SRE) has received growing attention in psychological discourse and research in recent years. It reflects both adaptive (assertive) and pathological (restricted or inflated) attitudes to the assertion of needs and rights and has not been studied in adult CSA survivors. The purpose of this study was to examine associations between CSA, attachment orientations, SR, and SRE. Sixty-seven Israeli women aged 25 ± 3.95 years (30 adult CSA survivors and 37 healthy female controls with no history of CSA) completed a demographic questionnaire and self-reported measures of adult attachment orientations, sense of entitlement in romantic relationships, and adult SR. CSA survivors reported greater attachment anxiety and attachment avoidance, more restricted SRE, and higher revictimization rates than control women. No difference was found between the groups in inflated SRE. In the CSA but not the control group, anxious and avoidant attachment orientations were significantly and negatively associated with assertive SRE. Insecure (anxious and avoidant) attachment fully mediated the association between CSA and restricted SRE. Our findings suggest that the interplay between insecure attachment and CSA is related to a sense of impaired assertive entitlement and elevated restricted entitlement in adult CSA survivors. This entitlement pattern can be destructive to survivors' romantic relationships and should be addressed in therapy.